Propuesta metodológica como apoyo al aprendizaje de creación de assets para videojuegos, a través de la utilización de técnicas 3d - Paredes Molina, Isaac Andrés (2023)
3D modeling is a technique that can be well known for the development of three dimensional printing or directly for video games, today has become part of advertising arts, to capture all the striking elements and acclaimed by gamers in something palpable, collectibles, toys, etc. Giving great relevance to modeling. This research seeks to define a schematic process to generate an orderly and analytical path, leaving aside the mechanical methods where the student does not learn, only memorizes. On the other hand, gamification is a fundamental concept included in this project, it helps to maintain dynamism and concentration within classes, developing greater attention and interest in learning the subject that the teacher will dictate. According to the data collection, more information was obtained from the interviews to expand the concepts in the theoretical bases, followed by surveys to professional experts in 3D modeling and on the other hand to pedagogical teachers, which helped to define the process to be followed to better produce the 3D proposals, at the end a focus group was developed, which defined the usefulness, understanding and level of attention they would pay when a learning methodology such as the one proposed in this project was presented